Neurosyphilis in interwar period in Lithuania: etiology, symptoms, diagnosis, and treatment methods - Jukna , Š.; Sakalauskaitė-Juodeikienė, E. (Neurologijos seminarai, 2020)
Neurosyphilis was an incurable and in most cases fatal disease until the beginning of the antibiotic era. The aim of this paper is to find out how the etiology and clinical symptoms of neurosyphilis were perceived, what diagnostic and treatment methods were used in Lithuania in the interwar period (1920-1939). We analyzed the first scientific medical journal Medicina in Lithuania and Baltic States. The main cause of neurosyphilis in the interwar period was identified as a consequence of untreated or undertreated syphilis. Wasserman, Pandy and Nonne-Apelt globulin reactions, as well as evaluation of cerebrospinal fluid cytosis were the most commonly used laboratory tests to diagnose the disease. Heavy metal therapy (arsenic, bismuth, mercury salts) and fever therapy (injections of the malaria agent, boiled cow’s milk, neobenzinol and pyrifer) were used to treat neurosyphilis in Lithuania in the period of 1920-1939.
Keywords: neurosyphilis; salvarsan; fever therapy; malaria; journal Medicina; interwar period; Lithuania